PENGARUH RETURN ON ASSET, EARNING PER SHARE, DAN USIA PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN OTOMOTIF YANG TERDAFTAR DI BURSA EFEK INDONESIA - Afifah, Siti Fira; Damayanti (JURNAL EKONOMI, 2022)
This study aims to prove the effect of Return on Assets, Earning Per Share, and company age on firm value in automotive companies listed on the Indonesia Stock Exchange. This study uses the dependent variable of firm value, while the independent variables are Return on Assets, Earnings Per Share, and company age. Data collection techniques in the research conducted using the documentation method. The population used is all automotive companies listed on the Indonesia Stock Exchange in 2016-2020. The sampling method is the purposive sampling method, in order to produce samples according to the research criteria. The research sample consisted of 9 companies with 45 observations. The data analysis technique used by the researcher was multiple linear regression analysis. Prior to the previous regression, it was tested with the classical assumption test to obtain the best linear unbias estimate (BLUE) data. Based on the results of the study indicate that Return on Assets has a positive and insignificant effect on company value on automotive companies listed on the Indonesia Stock Exchange, Earning Per Share has a significant positive effect on company value on automotivecompanies listed on the Indonesia Stock Exchange and company age has an insignificant negative effect on the value of the company. The determination test shows the adjusted R2 value of 0.172, meaning that the firm value variable can be explained by the three independent variables Return on Assets, Earning Per Share, and company age of 17.2%, while the remaining 82.6% in this study is explained by other factors that are not included in the regression model.